PENGARUH SHOPPING LIFESTYLE DAN FASHION INVOLVEMENTTERHADAP IMPULSE BUYING BEHAVIOR - Marthasari, Garnis; Yulinda, Ade Tiara (Creative Research Management Journal, 2024)
This research aims to find out how Shopping Lifestyle and Fashion Involvement influence the Impulse Buying Behavior (case study of consumers at the Gallery RJ store in Bengkulu City). The research method used was quantitative, with a sample of 96 respondents from Gallery RJ buyers. Data analysis includes the Classic Assumption Test, Multiple Linear Regression, Coefficient of Determination (R2), and Partial tests (t test), Simultaneous (F test). The research results show that Shopping Lifestyle has a significant and positive influence on Impulsive Buying Behavior H1 is accepted, likewise Fashion Involvement also shows a significant positive influence on Impulsive Buying Behavior H2 is accepted. Meanwhile, the F Shopping Lifestyle (X1) and Fashion Involvement (X2) tests have a significant influence on Impulse Buying Behavior (Y) at Gallery RJ Bengkulu City so that H3 is accepted. The coefficient of determination shows that together Shopping Lifestyle and Fashion Involvement make a big contribution in influencing Impulsive Buying Behavior at Gallery RJ Bengkulu City. And the most dominant factor with the largest regression coefficient value is the Fashion Involvement variable (X2)